To check your answer substitute it into each equation. Putting x = 2 into the first equation 3x-2y = -11 gives 6-2y=-11, 17=2y, y=17/2. Putting x = 2 into the second equation x = 2y-9 gives 2 = 2y-9, 11=2y, y=11/2. These are not consistent so x=2 cannot be correct.

Write your two equations as

3x - 2y = -11

x - 2y = -9

Subtract the second from the first

2x = -11 - (-9) = -2

x = -1

Substitute into each equation

-3 - 2y = -11: y = 4 and

-1 = 2y - 9: y = 4. These are consistent. So x=-1, y=4.